Source Sink Matching for Field Scale CCUS CO2-EOR Application in Indonesia - Usman Usman; Dadan DSM Saputra; Nurus Firdaus (Scientific Contributions Oil and Gas, 2021)
The carbon capture utilization and storage (CCUS) referred in this paper is limited to the use of CO2 to the enhanced oil recovery (CO2-EOR). The CCUS CO2-EOR technology can magnify oil production substantially while a consistent amount of the CO2 injected remains sequestrated in the reservoir, which is beneficial for reducing the greenhouse gas emission. Therefore, this technology is a potentially attractive win-win solution for Indonesia to meet the goal of improved energy supply and security, while also reducing CO2 emissions over the long term. The success of CCUS depends on the proper sources-sinks matching. This paper presents a systematic approach to pairing the CO2 captured from industrial activities with suitable oil fields for CO2-EOR. Inventories of CO2 sources and oil reservoirs were done through survey and data questionnaires. The process of sources-sinks matching was preceded by identifying the CO2 sources within the radius of 100 and 200 km from each oil field and clustering the fields within the same radius from each CO2 source. Each cluster is mapped on the GIS platform included existing and planning right of way for trunk pipelines. Pairing of source-sink are ranked to identify high priority development. Results of this study should be interest to project developers, policymakers, government agencies, academicians, civil society and environmental non-governmental organization in order to enable them to assess the role of CCUS CO2-EOR as a major carbon management strategy.